Astronomical constraints on the duration of the early Jurassic Hettangian stage and recovery rates following the end-Triassic mass extinction (St Audrie's Bay/East Quantoxhead, UK) - Ruhl, M; Deenen, M; Abels, H; Bonis, N; Krijgsman, W; Kürschner, WM (2010)
The end-Triassic environmental crisis with major extinctions in the marine realm is followed by successive recovery in the lower Jurassic Hettangian Stage. Accurate timing of events is however still poorly constrained. In this study, combined field observations and physical and chemical proxy records, covering the uppermost Triassic and lower Jurassic marine successions of St Audrie's Bay and East Quantoxhead (UK), have been used to construct a floating astronomical time-scale of ~2.5Myr in length. This time-scale is based on the recognition of meters thick cycles in limestone and (black) shale predominance and concurrent variability in physical and chemical proxy records. Three to five individual black-shale beds occur within these meter-scale sedimentary bundles and are interpreted to reflect precession-controlled changes in monsoon intensity, while the bundles are interpreted as forced by the ~100-kyr eccentricity cycle. On the basis of these findings, we propose an astronomically constrained duration of the Hettangian stage of 1.8Myr in the UK and unequal duration of Hettangian ammonite zones (Psiloceras planorbis zone: ~250kyr; Alsatites liasicus zone: ~750kyr; Schlotheimia angulata zone: ~800kyr). Within this astronomical framework, the extinction interval and coinciding negative CIE represent 1 to 2 precession cycles (~20-40kyr). The amount of time succeeding the end-Triassic negative carbon isotope excursion (CIE) and preceding the first Jurassic ammonite occurrence (in the UK) is constrained to 6 climatic precession cycles (~120kyr). Cyclostratigraphic correlation to the astronomically-tuned sedimentary record of the continental Newark basin (USA) allows to locate the stratigraphic position of the marine defined Triassic-Jurassic and Hettangian-Sinemurian boundary in the continental realm. Continuous low δ13CTOC values throughout the Hettangian and early Sinemurian, succeeding volcanic activity in the Central Atlantic Magmatic Province (CAMP), may suggest a long-term change in Earth's global biogeochemical cycles, which do not fully recover for several million years. © 2010 Elsevier B.V.